Feminisme Kristen bagi Komunitas Perempuan Inklusif: Sebuah Kontribusi Elizabeth Schüssler Fiorenza terhadap Etika Solidaritas - Sumual, Ivonne Sandra; Yemima Pasulu (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2024)
Elizabeth Schüssler Fiorenza offers a new paradigm in feminist theology through the concepts of kyriarchy and ekkl?sia of wo/men, which serve as critiques of patriarchal domination within the church and society. This study addresses the relevance of Fiorenza's thoughts in deconstructing the patriarchal structures embedded in Indonesian churches, which often perpetuate gender-based discrimination and hinder women's full participation in religious and social life. This research employs a qualitative approach with a literature review method to analyze Fiorenza's works and their relevance within Indonesia's social, cultural, and religious contexts. The findings reveal that Fiorenza's feminist hermeneutics can serve as a tool for ecclesiastical transformation by reinterpreting biblical texts in a more inclusive and relevant manner. The concept of ekkl?sia of wo/men provides a model for an egalitarian faith community, enabling churches to create inclusive spaces for women. Inclusive solidarity ethics offers concrete steps for Indonesian churches to act as agents of social change, responding to the challenges of gender injustice. This study underscores the importance of church reform rooted in the principles of justice and inclusion.